Brave enough - Strayed, Cheryl, 1968- (Knopf, 2015)
"From the best-selling author of Wild, a collection of quotes--drawn from the wide range of her writings--that capture her wisdom, courage, and outspoken humor, presented in a gift-sized package that's as irresistible to give as it is to receive. Around the world, thousands of people have found inspiration in the words of Cheryl Strayed, who in her three prior books and in her "Dear Sugar" columns has shared the twists and trials of her remarkable life. Her honesty, spirit, and ample supply of tough love have enabled many of us, even in the darkest hours, to somehow put one foot in front of the other--and be brave enough. This book gathers, each on a single page, more than 100 of Strayed's indelible quotes and thoughts--"mini instruction manuals for the soul" that urge us toward the incredible capacity for love, compassion, forgiveness, and endurance that is within us all. Be brave enough to break your own heart. You can't ride to the fair unless you get on the pony. Keep walking. Acceptance is a small, quiet room. Romantic love is not a competitive sport. Forward is the direction of real life. Ask yourself: What is the best I can do? And then do that"--